Balitok (Gold) a research-based documentary on artisanal and small-scale mining in Nueva Vizcaya - Andes, Sheryl Rose Mariquit
"Documentary as a form of non-fiction film exists to serve a number of roles. It is useful in providing an insight or shedding a light on that which is unknown, it can be used to educate others on important topics, it is a useful tool in the exploration and understanding of people and cultures, and it can be the instigator of political or social change. Documentary can be used to keep a record of an event or to construct a narrative coherence between numerous events and people (McGinn 2009). The study combines both discipline of research and non-fiction film to discuss the issue of Mining in the Philippines. The study presents two arguments; Mining contributes to the economy in terms of increased employment, foreign exchange earnings and, tax revenues (The Wallace Business Forum, Inc. 2003). However, Mining also has great impacts not only to the communities within and near the mining operations, but mostly on water and other natural resources (Alyansa Tigil Mina [Alliance to Stop Mining], 2010). Guided by the frameworks of Documentary, Third Cinema and Cultural Hegemony, the research and documentary brings the viewer to the world of artisanal and small-scale mining sector (particularly Indigenous People). The documentary utilized Bill Nichol's observational and reflexive mode combined the techniques on third cinema in following the laborious process/stages of mining a gold or Balintok in Ilocano language. The documentary captures the life, struggles and triumphs of Kankanaey boy named Ongan and Kalanguya woman named Mona from the mineral rich community; Barangay Runruno, Municipality of Quezon City, Nueva Vizcaya. The study emphasizes the role of research as main foundation of the documentary. The research combines social and development research methodologies, which includes participant observation, community integration, historiography and purposive sampling to represent the critical milieu in the mining industry."
Vita.
Thesis (M.A. Media Studies (Film)) -- University of the Philippines, Diliman.
Keywords: Mineral industries -- Philippines -- Nueva Vizcaya; Mines and mineral resources -- Philippines -- Nueva Vizcaya; Documentary films